'Putting heart' into history and memory: Dialogues with Maya-Tseltal philosopher, Xuno López Intzin. (October 2020) - Hernández Castillo, R Aída
In this article, the author shares her dialogues with the Maya-Tseltal scholar Xuno López Intzin, to open an analytical window to Non-Western conceptions of memory and time. It focuses on the cyclical conceptualization of time, and the embodied experience of history and memory of Maya peoples in the Chiapas Highlands. This Mayan perspective is explained by Xuno López Intzin, in an analytical dialogue with the author, who questions her own linear ethnohistorial perspectives. It aims to contribute to the decolonization of memory studies by giving an academic platform to this subaltern, nonlinear conception of time and history.